2009
DOI: 10.1111/j.1468-0343.2009.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Stock Returns Vary With Campaign Contributions? Bush vs. Gore: The Florida Recount

Abstract: I examine the relation between campaign contributions and stock returns during the Florida recount period of the 2000 presidential elections. Using the full population of publicly traded firms, I find an economically significant positive (negative) relation between pre-election campaign contributions to Bush (Gore) and stock returns during the 37-day election recount period. This relation exists for both the level and partisanship of contributions, and exists incrementally at both the firm and industry levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…20. Our findings are consistent with those of Shon (2010) and Fisman (2001). Shon examines the relationship between campaign contributions and stock returns during the Florida recount period of the American presidential elections in 2000.…”
Section: Discussionsupporting
confidence: 93%
“…20. Our findings are consistent with those of Shon (2010) and Fisman (2001). Shon examines the relationship between campaign contributions and stock returns during the Florida recount period of the American presidential elections in 2000.…”
Section: Discussionsupporting
confidence: 93%
“…8 Even though the majority of studies find that political connections are beneficial for firms, some studies show that corporate political connections are costly due to rent-seeking by politicians (see Morck, Stangeland, and Yeung, 2000;Thesmar, 2006a, 2006b;Fisman, Fisman, Galef, and Khuranna, 2006;Fan, Wong, and Zhang, 2007). 9 See also Knight (2006), Shon (2006), and Jayachandran (2006) for evidence that firms benefit from political contributions. On the other hand, Ansolabehere, de Figueiredo, and Snyder (2003), Ansolabehere, Snyder, and Ueda (2004), and Hersch, Netter, and Pope (2008) show that political contributions have no significant impact on legislator voting behavior and on firm valuation.…”
Section: Introductionmentioning
confidence: 97%
“…There are similar papers whose goal was to measure the effect of election results on the stock market - Vuchelen (2003) analysed a Belgium example of the effect of a coalition government on the stock market, whereby he concluded that the market reaction would depend on the political affiliation of the parties (left-wing, right-wing, or centre) that constitute the government. Shon (2010) analysed the impact of the American presidential system during the recounting of presidential ballots in Florida in 2000, which determined the outcome of the election. During this period, Shon noticed a positive abnormal return with companies that funded Bush`s campaign and a negative one with those funding Al Gore`s campaign.…”
Section: Introductionmentioning
confidence: 99%